Mastering Properties of Organic Compounds through Activity-Based Teaching Technique - Edwin, Byusa; Edwige, Kampire; Adrian, Mwesigye Rwekaza (African Journal of Educational Studies in Mathematics and Sciences, 2021)
Some learners perceive chemistry as a complex subject to learn, saying teaching is boring and not enjoyable. There is a need for making the learning experience more enjoyable to make chemistry easy to understand. This study aims to assess the effect of activity-based teaching techniques compared to the conventional technique on the performance of students in chemistry. The study was quasi-experimental-based research using both pre and post-test, achievement tests. The sample comprised 166 students, as a total number of students in four classes, from a population of 1610 students of the second grade of secondary classes (S2) studying the Properties of Organic Compounds and Uses of Alkanes. Pre-test was conducted, and its data was collected before the intervention, and the post-test was conducted and data was collected after the intervention. Both the descriptive and inferential statistical tests were applied in the analysis. Students’ performance gain in chemistry was higher in the treatment classes as the mean value was 6.81 and the standard deviation was 1.66 (M = 6.81, SD = 1.66) than that of the comparison classes (M = 6.35, SD = 1.78). However, difference was not significant, t(164) = -1.73, p = .085. Teachers should be supported in designing physical pedagogical activities for improving learning outcomes in chemistry.
Keywords: Activity-based teaching techniques; Chemistry; Conventional teaching techniques; Organic chemistry; Secondary school